THE EFFECT OF USING VIDEOSCRIBE MEDIA ON STUDENT LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS SMPN 2 BANDAR MASALAM SIMALUNGUN REGENCY - Jusua Barus; Siti Nurfadillah Siregar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This type of research is quantitative research with an experimental method approach.The results of the research in this thesis, in this study, the experimental class that was taught using videoscribe media obtained an average learning outcome for Islamic Religious Education. The results of the posttest in the experimental class show that the highest score is 92 and the lowest score is 60, this indicates a significant increase compared to the pretest results in the experimental class. Whereas in the control class the highest score is 90 and the lowest score is 40, this means that there is an increase in learning outcomes but not significant in the control class. Based on the results of research that has been conducted by researchers, it can be concluded that learning using Videoscribe media can have a positive effect on educational learning outcomes Religion of Islam (PAI). This can be seen from the results of hypothesis testing at a significant level of 5% (α = 0, 05). testing the hypothesis on the posttest data of the experimental group in the output table of the paired samples test above, it is known that the Sig. (2-tailed) is 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be seen that there is an average difference between pretest and posttest learning outcomes, which means there is an effect of using videoscribe media on student learning outcomes in Islamic religious education subjects at SMP Negeri 2 Bandar Masilam.